Pemanfaatan Penggunaan Slims di UPT Perpustakaan Politeknik Negeri Lhokseumawe - Khoirunnisaa Khoirunnisaa; Abdi Mubarak; Muhammad Dalimunte (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The objectives to be achieved from this research are to identify obstacles, improve the role of library managers and the Library Management system, and find out the strengths and weaknesses of SLiMS. This research method uses a qualitative approach. using data collection techniques through interviews, observation and documentation. The informant in this research was the Lhokseumawe State Polytechnic UPT librarian who the researcher had selected according to the research subject criteria. As a result of this research, it can be said that the understanding of Lhokseumawe State Polytechnic UPT librarians regarding the use of SLiMS can be said to be understood by librarians regarding the use of SLiMS. However, managers can operate the software even with limited capabilities. The obstacle to using SLiMS at the UPT of the Lhokseumawe State Polytechnic Library is understanding the technology because they are not used to it and it also comes from human resources (human resources). The task of library managers is to recruit effective human resources and effective career development. Advantages and Disadvantages of SLiMS 7. One of its advantages is that it makes the work of librarians easier and faster in each service. The disadvantage is that if the light goes out, the system cannot be used manually and the software must be able to use a stable network so that it can be used.